Analysis of the dynamics of IPO transactions in the banking sector - V. A. Belyaev (Финансы: теория и практика)
IPO (initial public offering) is a widespread financing instrument in the world, however, the scientific community pays little attention to the dynamics of IPOs in the banking sector. The aim of the study is to critically analyze the dynamics of IPO transactions of credit institutions on the horizon from January 1, 2000, to December 31, 2020. The research methodology includes analytical methods for collecting and processing information, comparative and graphical analysis of the database collected by the author and consisting of 305 IPOs of banks from 2000 to 2020. The study compares the dynamics of IPO transactions of credit institutions from developed and developing countries, identifies characteristics inherent in each market, and explains the differences in market dynamics. The study reveals clustering in the IPO market of credit institutions and compares clustering with the general market of initial public offerings. It is shown that lending institutions around the world have actively attracted funds through IPO, having placed their shares for a total of $ 218 billion. The bulk of the funds were attracted by banks from emerging markets, primarily from China. During this period, there were 3 IPO waves on the banking IPO market, characterized by a significant increase in placement volumes and profitability on the first day of trading. This clustering in the IPO market of credit institutions was not typical only for the banking sector but coincided with the global growth in the number of transactions and IPO yields. The author concludes that the placement of shares of credit institutions during the hot market period is the most promising in terms of the volume and dynamics of raising funds; the IPO market of credit institutions retains high growth potential, primarily in Asia and the CIS.